Technology Integration in ESL Classroom: Advantages and Challenges (International Journal of Language, Literacy and Translation, 2025)
This study aims at identifying the emerging trends of technology integration, and the potential advantages and contributing obstacles in the domain of English as a second language (ESL) learning and teaching. The advantages of technology integration in ESL learning were examined in the Pakistani context. The data was collected from 10 ESL teachers through semi-structured interviews. This qualitative study employed a thematic analysis technique to figure out the advantages and obstacles of using technology among participants. The findings of the study shed light on some advantages including opportunities to take online tests and quizzes, the ability to answer the question immediately, to improve grades in English tests and assignments, to foster collaboration and independent learning, and to improve English language in terms of receptive and productive skills. However, the current study also highlights some obstacles in relation to technology integration in ESL learning such as the evolutionary nature of technology, appropriateness of tools in use, availability of the resources, and familiarity with the rapid technological advancements.